Ecotourism activities: threats to sustainability of Belum Temengor Forest Complex (BTFC)natural heritage? - Azreen Rozainee Abdullah; Chan , Ngai Weng (Environmental Management Society, Malaysia, 2011)
Ecotourism activities in Belum Temengor Forest Complex (BTFC)heavily rely on its rich and diverse natural heritage to lure in tourist.Located on the central forest spine in Peninsula Malaysia, This area is blessed with abundant natural heritage and extremely sensitive to human disturbance. The natural attractions in the area are also highly susceptible to over-exploitation, miss-used and mis-management by parties with vested interest and care less about the environment. Ecotourism in BTFC holds great potential to be one of the best international ecotourism destinations and the Malaysian Nes Economic Model sees this opportunity in as a neww niche to increase tourism influx, attract foreign currency and generates revenue for the country . Although the Malaysian government is pushing for a world class ecotourism destination development in BTFC, precoutionary actions must be engaged to regulate and sustain the rapid development in order to keep the attractiveness of the natural heritage last forever. Its is also crucial to minimize possible threats posed by ecotourism activities that could harm the attractiveness of the natural heritage and jeopardise its operation in the long run. Acknowledging yhe importanceof the rich natural heritage to be preserved at its best, this paper reviews possible environmental threats posed by power boating and camping in BTFC, the effects of the activities on the sensitive environment, highlights the existing management strategies and provides possible solutions to minimize the threats.